Implementing buprenorphine prolonged-release injection using a health at the margins approach for transactional sex-workers - Gittins, Rosalind; Teck, Joseph Tay Wee; Knowles, Rebecca; Clarke, Nicole; Baldacchino, Alexander (Frontiers in Psychiatry, 2023)
Abstract Background Access to prescribed interventions and retention in treatment services are associated with improved health outcomes and reduced premature mortality rates for people living with opioid use disorder (OUD). In Leeds, transactional sex-workers frequently cycled in and out of treatment for OUD such that they never reached a level of engagement that permitted opportunities to meet their healthcare or housing needs. Barriers to accessing care provision include an itinerant lifestyle, difficulties with travel at unpredictable hours, impacting upon adherence to medication regimens including daily supervised consumption. Objectives To use a co-produced, ‘health at the margins’ approach, to reach the sex-working population in Leeds, and support informed choices about the potential to receive buprenorphine prolonged release injection (BPRI) as a treatment option for OUD. Methods BPRI was introduced using a theory of change model and improvements in sex-worker care delivery was reviewed. Strategies included buprenorphine micro-induction, shared decision-making, collaborative multi-agency working and supporting a strengths-based and trauma-informed approach. Results Benefits of BPRI included removal of the need for daily pharmacy visits, reducing the risk of diversion, improved medication adherence, stability and engagement with treatment and supportive services. Conclusions BPRI may offer an additional option for pharmacological interventions for people with OUD where there may be increased barriers to accessing treatment for example due to sex-working. Strategies for effective BPRI include micro-induction, shared decision-making, collaborative multi-agency working and supporting a strengths-based approach.